1987
DOI: 10.1159/000174221
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Chagas’ Heart Disease in the Elderly: A Clinicopathologic Study

Abstract: A retrospective study of the medical records of our hospital from 1965 to 1985 was carried out to characterize for the first time chronic Chagas’ heart disease in the elderly (more than 70 years old). A total of 25 patients (mean age = 76) were suitable for the study. Congestive heart failure, sudden cardiac death, thromboembolism and atypical chest pain were found in 68, 16, 8 and 8% of cases, respectively. Ventricular premature contractions (60%), right bundle branch block (32%), left anterior hemiblock (28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…16 Autopsy studies have revealed that pulmonary embolism may be found in up to 37% of patients who died of CHF secondary to Chagas cardiomyopathy. 20 Intractable pump failure appears to be the most important cause of death in patients with Chagas disease heart failure, mainly in those with advanced forms of the disease, 21 affecting up to 43% of patients with this condition.…”
Section: Clinical Characteristics Of Chf Secondary To Chagas Cardiomymentioning
confidence: 99%
“…16 Autopsy studies have revealed that pulmonary embolism may be found in up to 37% of patients who died of CHF secondary to Chagas cardiomyopathy. 20 Intractable pump failure appears to be the most important cause of death in patients with Chagas disease heart failure, mainly in those with advanced forms of the disease, 21 affecting up to 43% of patients with this condition.…”
Section: Clinical Characteristics Of Chf Secondary To Chagas Cardiomymentioning
confidence: 99%
“…Because there is no undisputable effective treatment for chronic infection, despite the effectiveness of the control measures, the disease might remain a public health problem for some decades among older subjects, through the operation of a cohort effect [4]. The effect of T. cruzi infection on the elderly has hardly been studied [4][5][6][7][8][9] and deserves more attention from the scientific community and from policy makers. Impairment of cardiac vagal modulation has been consistently reported in ChD [10][11][12][13] and may be related to both autoimmune and inflammatory mechanisms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Chagas' heart disease is estimated to affect 10 million people in South America [1], The clinical manifestations of Chagas' heart dis ease are congestive heart failure, sudden car diac death, thromboembolic phenomena, atypical chest pain and arrhythmias [2][3][4],…”
Section: Introductionmentioning
confidence: 99%